Analysis of Whole Machine Running Load Test and Optimization of Large Wind Turbine Under Complex Terrain - Wei Yufeng; Chen Baokang; Yu Gaoyang; Shi Yufeng (Jixie chuandong)
With the gradual popularization and maturity of wind energy resources exploitation and utilization technology,the installation and running environment of large wind turbine gradually develop from conventional flat terrain to complex terrain,which result to worse operation conditions and more uncertain inflections.So it is very necessary to test load of wind turbine when the whole machine is running under complex terrain. A3. 0 MW wind turbine in Guangxi Gongcheng wind field is chosen as the testing object,together with special test scheme,based on the MATLAB software development procedure to analyze the testing data. The rain flow method is used to get the load statistics of blade and tower tube and the 10 min-equivalent load scattering plot.Comparing load optimization quantity and dynamic characteristic of conventional group and that of group with optimized strategy,the results indicated that load optimization changed load characteristic that helped to prolong the fatigue life of wind turbine. It has great significance for the guidance of large wind turbine installation and operation under complex terrain and can provide further support for research and manufacturing of large wind turbine model suitable for complex terrain.